The global burden of cardiovascular disease attributable to high alcohol use from 1990 to 2021: an analysis for the global burden of disease study 2021 - Chaofeng Niu; Juwei Dong; Peiyu Zhang; Qiwen Yang; Donghua Xue; Birong Liu; Di Xiao; Rui Zhuang; Meng Li; Lijing Zhang (Frontiers in Public Health)
BackgroundCardiovascular diseases (CVDs) are the leading global disease burden, with alcohol consumption closely linked to their occurrence. This study analyzes data from the Global Burden of Disease Study 2021 (GBD 2021) to assess the distribution and trends of high alcohol use-related CVD from 1990 to 2021 across global, regional, and national levels.Materials and methodsWe used the data from the GBD 2021 to conduct stratification by region, country, gender, age, SDI, and disease type in terms of the number of deaths, age-standardized mortality rate (ASMR), disability-adjusted life years (DALYs), age-standardized rate of DALYs (ASDR), years lived with disability (YLDs), age-standardized rate of YLDs, years of life lost (YLLs), and age-standardized rate of YLLs to comprehensively assess the burden of high alcohol use-related CVD from 1990 to 2021. All statistical analyses in this study were performed using R statistical software (version 4.1.2).ResultsBetween 1990 and 2021, global deaths, DALYs, YLDs, and YLLs attributable to high alcohol use-related CVD showed notable variation. By 2021, global deaths had doubled compared to 1990, while ASMR, ASDR, age-standardized YLD rate, and YLL rate all declined. Eastern Europe had the highest rates in 2021. Males consistently had higher ASMR, ASDR, YLD, and YLL rates compared to females, with the highest number of deaths occurring in the 70–74 age group, and the 65–69 age group showing the highest DALYs, YLDs, and YLLs. These rates increased with age. Stroke was the most common high alcohol use-related CVD, while ischemic heart disease (IHD) was the least common.ConclusionBetween 1990 and 2021, the overall burden of high alcohol use-related CVD declined globally, though some regions experienced an increase. This highlights the need for continued public health efforts, particularly targeting high-risk regions and populations, to mitigate the impact of alcohol on cardiovascular health.